Relationship Between Spatial Reasoning Skills and Digital Puzzle Games - Nicolaidou, Iolie; Chrysanthou, George; Georgiou, Marita; Savvides, Christos; Toulekki, Stavrini (My University, 2021)
Spatial relations are an integral component of science, technology, engineering, and mathematics (STEM) disciplines. Despite studies indicating that spatial reasoning skills are important for student success in STEM disciplines, these are not systematically instructed or tested in K–12 education. There are very few widely available opportunities to train spatial reasoning skills that have been proven to be effective tools. Previous studies have found a connection between playing action games and increased spatial skills. Recently, the connection between puzzle games and spatial skills has received attention, as a positive relationship between them was found in school children. The present study implemented a survey research design to examine whether there is a difference among young adults (18-30 years old) with respect to their spatial reasoning skills. The main focus of the study was a comparison between players of puzzle games as compared with nongamers. For this purpose, a questionnaire was developed that tested spatial reasoning skills (locating patterns, finding symmetry, matching shapes etc.), using ten multiple-choice problems. Fifty-one participants (31 male), with an average age of 22.6 years old (SD=3.48) completed the questionnaire. Data analysis indicated that the number of hours of playing digital puzzle games had a strong, statistically significant positive relation with spatial reasoning skills (Pearson’s r= 0.51, p<0.01). This provides an indication that the more hours young adults play digital puzzle games the higher their spatial reasoning skills. The study did not find a statistically significant correlation between spatial skills and variables such as self-perceived programming knowledge, or frequency of playing non-digital puzzle games. This study argues in favor of the design and development of mobile puzzle games that seamlessly promote spatial skills from a young age, without the need to provide structured formal education interventions for K-12 children. Findings are valuable for game designers and developers as they indicate benefits of playing digital puzzle games.
Keywords: spatial reasoning skills; spatial visualization skills; puzzle games; digital games